Associations between back pain across adulthood and spine shape in early old age in a British birth cohort. Issue 1 (December 2018) - Muthuri, Stella; Pavlova, Anastasia; Saunders, Fiona; Hardy, Rebecca; Gregory, Jennifer; Barr, Rebecca; Martin, Kathryn; Adams, Judith; Kuh, Diana; Aspden, Richard; Cooper, Rachel
Abstract We aimed to examine whether back pain across adulthood was associated with spine shape at age 60–64 years. Data were from 1405 participants in the MRC National Survey of Health and Development, a nationally representative British birth cohort. Back pain was ascertained during nurse interviews at ages 36, 43, 53 and 60–64 years. Cumulative exposure to back pain was then derived by counting the number of ages at which back pain was reported. Statistical shape modelling was used to characterise thoracolumbar spine shape using lateral dual-energy x-ray absorptiometry images which were ascertained at age 60–64 years. Linear regression models were used to test associations of spine shape modes (SM) with: (1) cumulative exposure to back pain; (2) back pain reports during different periods of adulthood. After adjusting for sex, higher cumulative exposure to back pain across adulthood was associated with wedge-shaped L4-5 disc (lower SM4 scores) and smaller disc spaces (higher SM8 scores) in both sexes. In addition, reporting of back pain at ages 53 and/or 60–64 years was associated with smaller L4-5 disc space (lower SM6 scores) in men but not women. These findings suggest that back pain across adulthood may be associated with specific variations in spine shapes in early old age.